2010
DOI: 10.1071/ch09580
|View full text |Cite
|
Sign up to set email alerts
|

Design, Synthesis, and Cytotoxicity of Indolizinoquinoxaline-5,12-dione Derivatives, Novel DNA Topoisomerase IB Inhibitors

Abstract: A series of new indolizinoquinoxaline-5,12-dione derivatives were designed and synthesized via a heterocyclization reaction of 6,7-dichloroquinoxaline-5,8-dione with active methylene reagents and pyridine derivatives. The synthesized compounds exhibited significant activity to inhibit the growth of four human tumour cell lines, including lung adenocarcinoma cell, large-cell lung carcinoma cell, breast carcinoma cell, and ardriamycin-resistant breast carcinoma cell at micromolar range. These compounds were also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 21 publications
0
1
0
Order By: Relevance
“…Structure activity relationships (SAR) evaluation indicated that the nitrogen atomin the A ring played an important role for cytotoxicity. N,N-syn isomer exhibited higher cytotoxicity and Top1 inhibitory activity than N,N-trans isomer or the corresponding derivatives with two nitrogen atoms in the A ring, such as indolizinophthalazinediones and indolizinoquinoxalinediones [10,11]. This led us to propose that the aminoalkyl side chain enhanced the cytotoxicity and Top1 inhibitory activity of the parent molecule possibly because the cationic side chain under physiological condition could improve cellular uptake and interactions with the Top1-DNA complex [12-15].…”
Section: Introductionmentioning
confidence: 99%
“…Structure activity relationships (SAR) evaluation indicated that the nitrogen atomin the A ring played an important role for cytotoxicity. N,N-syn isomer exhibited higher cytotoxicity and Top1 inhibitory activity than N,N-trans isomer or the corresponding derivatives with two nitrogen atoms in the A ring, such as indolizinophthalazinediones and indolizinoquinoxalinediones [10,11]. This led us to propose that the aminoalkyl side chain enhanced the cytotoxicity and Top1 inhibitory activity of the parent molecule possibly because the cationic side chain under physiological condition could improve cellular uptake and interactions with the Top1-DNA complex [12-15].…”
Section: Introductionmentioning
confidence: 99%
“…The MTT assay showed that compound 131 containing pyrazine showed significant inhibitory effects on HCT116, CCRF-CEM, A549, Huh7, and DU-145 cell lines, with IC50 values ranging from 1.61 to 13.15 µM[136].Shen et al designed and synthesized a series of new Indolizinoquinoxalin-5,12-dione derivatives. Compounds 132-134 showed significant inhibitory effects on the growth of four human tumor cell lines (GLC-82, NCI-H460, MCF-7, and MCF-ARD), with IC50 values ranging from 0.20 to 16.46 µM[137].Devi et al synthesized a series of new anthraquinone-based copper (II) complexes. Nuclear targeting complex 135 showed significant cytotoxicity to cancer cells in visible…”
mentioning
confidence: 99%